Human capital management in the Municipalidad de Pillco Marca, Huánuco, 2019 - Salazar-Lucas, Yadith N. (2020)
The objective of this research was to describe human capital management in the Municipalidad de Pillco Marca, Huánuco, 2019. The study had a quantitative approach, with a descriptive, non-experimental, cross-sectional and prospective design. The population consisted of 80 workers and the sample was selected through a non-probabilistic sampling for convenience made up of 60 workers. In data collection, the general characteristics interview was applied as a technique and a previously validated human capital management measurement questionnaire was used as an instrument, and its reliability was corroborated and aligned with the ethical considerations of autonomy, beneficence, non-maleficence and justice. The results showed that 68.3 % (82) were female and 31.7 % (38) were male. In terms of age, 30 % (36) were young adults and 55 % (66) had a high school education. Regarding civil status, the cohabitants predominated, with 65% (78), and regarding religion, 55 % (66) were catholics. In human capital management: personnel admission, performance evaluation, personnel training, career development and human capital management, a level of 76.7 % (92), 78.3 % (94), 78.3 % (94), 80 % (96) and 78.3% (94) of efficiency was obtained, respectively. Finally, in human capital management, 78.3 % (94) had an efficient level, 8.3 % (10) a regular level and 13.3 % (16) a deficient level. It is concluded that the level of human capital management in the Municipalidad de Pillco Marca, Huánuco, predominated with 78.3 % (94) at the efficient level.